Doppler ultrasound in the estimation of the severity of pulmonary infundibular stenosis in infants and children. - Houston, A B (1986)
Pressure gradients estimated by Doppler echocardiography were compared with values obtained at cardiac catheterisation in 31 children (aged seven days to 16 years, mean 2 years 7 months) with pulmonary infundibular stenosis including 16 with tetralogy of Fallot. Various parasternal and subcostal positions were explored to obtain the maximum velocity of blood flow and the obstructive gradient was calculated from the modified Bernoulli formula. The gradient across the obstruction could be measured directly at the time of catheterisation in only 21 patients. The correlation coefficient for the Doppler and total measured gradients was r = 0.90 for catheter entry and r = 0.77 for catheter withdrawal. Doppler ultrasound, by measuring the total gradient from the right ventricle to the pulmonary artery, provides a non-invasive assessment of the severity of pulmonary stenosis, and in those with infundibular obstruction allowance need not be made for possible energy losses caused by the elongated obstruction or the presence of narrowing at more than one level.